2018
DOI: 10.4103/ija.ija_529_17
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension and post-operative outcome in renal transplant: A retrospective analysis of 170 patients

Abstract: Background and Aims:Renal transplant is the best possible treatment for patients suffering with end-stage renal disease (ESRD). Cardiovascular events are the commonest factors contributing to perioperative morbidity and mortality in this population. These patients have a high incidence (up to 60%) of pulmonary hypertension (PH) and that may affect the perioperative outcome.Methods:In this study, we aimed to study the impact of PH on perioperative outcome after renal transplant. PH was defined as patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
Order By: Relevance
“… 3 , 4 , 14 , 16 A commonly cited reason for this association is that patients with PH are more prone to perioperative hypotension which can lead to DGF and potentially failure. 35 However, we observed that the incidence of DGF (6/11 transplanted patients; 54.5%) in post‐transplant patients did not correlate with perioperative hypotension (3/11 transplanted patients; 27.2%); and that even patients who were at a goal mean arterial pressure (MAP) intra‐operatively were at risk for DGF. Therefore, need for dialysis in the immediate post‐operative setting did not portend a poor prognosis for graft function at 1‐year.…”
Section: Discussionmentioning
confidence: 89%
“… 3 , 4 , 14 , 16 A commonly cited reason for this association is that patients with PH are more prone to perioperative hypotension which can lead to DGF and potentially failure. 35 However, we observed that the incidence of DGF (6/11 transplanted patients; 54.5%) in post‐transplant patients did not correlate with perioperative hypotension (3/11 transplanted patients; 27.2%); and that even patients who were at a goal mean arterial pressure (MAP) intra‐operatively were at risk for DGF. Therefore, need for dialysis in the immediate post‐operative setting did not portend a poor prognosis for graft function at 1‐year.…”
Section: Discussionmentioning
confidence: 89%
“…Patients on tacrolimus have to avoid breastfeeding up to 4 hours after taking a dose. [ 10 ] Patients on cyclosporine are advised against breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Most HD patients with PH have impaired left ventricular systolic function, which increases the risk of developing heart failure [11]. In renal transplant recipients, patients with PH are more likely to experience perioperative hypotension and delayed graft function [12]. Given the dismal prognosis for PH in dialysis patients, the risk factors for death must be identified to plan strategies for early intervention.…”
Section: Introductionmentioning
confidence: 99%